The protective mechanisms underlying Ginsenoside Rg1 effects on rat sciatic nerve injury. Issue 19 (2nd October 2019) - Huo, Dong-Sheng; Sun, Jian-Fang; Cai, Zhi-Ping; Yan, Xu-Sheng; Wang, He; Jia, Jian-Xin; Yang, Zhan-Jun
ABSTRACT: Ginsenoside Rg1 (GsRg1), derived from the herb Ginseng, was found to exert protective effects in nerve injury; however, the mechanisms underlying these effects remain to be determined. Oxidant stress and apoptosis are known to be involved in sciatic nerve injury. Thus, the aim of this study was to examine whether GsRg1 was able to modify sciatic nerve injury in a rat model. The following parameters were measured: (1) number of spinal cord motoneurons by Nissl staining, (2) oxidation parameters including spinal cord malondialdehyde (MDA) levels and activities of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) as well as (3) involvement of apoptosis by determining caspase-3 and X-linked inhibitor of apoptosis protein (XIAP) by immunohistochemistry and Western blot. The number of spinal cord motoneurons was significantly reduced after sciatic nerve injury, while treatment with GsRg1 markedly elevated cell number. Sciatic nerve injury markedly increased spinal cord MDA content concomitant with reduced activities of SOD and GSH-Px. GsRg1 significantly decreased MDA content accompanied by elevated activities of SOD and GSH-Px. Further nerve injury significantly diminished protein expression levels of XIAP accompanied by elevated protein expression levels of caspase-3 in the spinal cord. GsRg1 markedly increased protein expression levels of XIAP, but significantly reduced protein expression levels of caspase-3. Data suggest that the protective effects of GsRg1 in sciatic nerve injury may be associated with reduced oxidative stress involving anti-apoptotic pathways.